Consumption of ultra-processed foods and female infertility: a cross-sectional study - Evans, Adam T.; Alur-Gupta, Snigdha; Martinez Steele, Euridice; Meng, Ying; Knutson, Alex J.; Vitek, Wendy S. (Frontiers in Public Health, 2025)
BackgroundA high dietary consumption of ultra-processed foods (UPF) has been associated with abnormal semen analysis parameters in males; however, it is unclear whether there is an impact on female reproduction. The objective of this study is to assess whether high consumption of UPF is associated with female infertility.MethodsA cross-sectional analysis of females aged 18–45 years who participated in the National Health and Nutrition Examination Survey (NHANES) from 2013 to 2018 was performed. Females were eligible for inclusion if they provided a 24-h dietary recall and responded to a question regarding infertility. Foods reported during a 24-h dietary recall were classified according to the Nova system. The relative percentage of total energy consumed from UPF and unprocessed/minimally processed foods within a 24-h period was calculated.ResultsThe prevalence of infertility was 11%. The overall mean percentage of daily UPF and unprocessed/minimally processed food intake among respondents was 57 and 29%, respectively. There was no difference in the odds of female infertility when comparing females in the lowest tertile of UPF consumption to peers in the middle [aOR = 1.37, 95% CI (0.96, 1.95)] or highest tertile of consumption [aOR = 1.26, 95% CI (0.91, 1.74)]. Similarly, there was no difference in the odds of infertility between participants in the middle [aOR = 1.39, 95% CI (0.83, 2.33)] or highest tertile [aOR = 0.73, 95% CI (0.34, 1.54)] of unprocessed/minimally processed food consumption relative to those in the lowest tertile. In an intermediate model removing body mass index (BMI) as a covariate, an increased odds of infertility was noted among females with the highest tertile of UPF consumption relative to those in the lowest tertile [aOR = 1.46, 95% CI (1.01, 2.09)].ConclusionAmong women of reproductive age, high consumption of UPF is associated with female infertility. BMI is a mediator of the association between UPF and female infertility.